2014
DOI: 10.1152/jn.00509.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activity in early visual areas predicts interindividual differences in binocular rivalry dynamics

Abstract: When dissimilar images are presented to the two eyes, binocular rivalry (BR) occurs, and perception alternates spontaneously between the images. Although neural correlates of the oscillating perception during BR have been found in multiple sites along the visual pathway, the source of BR dynamics is unclear. Psychophysical and modeling studies suggest that both low- and high-level cortical processes underlie BR dynamics. Previous neuroimaging studies have demonstrated the involvement of high-level regions by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Test-retest reliabilities 114 for average percept duration are moderate to high, with past stud-115 ies reporting r s = 0.69 (Whittle, 1963), r p = 0.7 (Miller et al, 2010) 116 and r p = 0.8 (Pettigrew & Miller, 1998, in bipolar patients and 117 controls). 118 Variability in rate of rivalry has been found to correlate with 119 patterns of saccadic eye movements (Hancock et al, 2012), with 120 level of dichoptic masking (Baker & Graf, 2009), with retinotopic 121 activity in extrastriate visual cortex triggered by the suppressed 122 image (Yamashiro et al, 2014), and with variability in the structure 123 of parietal cortex (Kanai, Bahrami, & Rees, 2010). Rate of rivalry is 124 faster in children than adults (Hudak et al, 2011;Kovacs & 125 Eisenberg, 2004) and declines with increasing age in adulthood 126 (Jalavisto, 1964;Ukai, Ando, & Kuze, 2003).…”
Section: Stereopsis 23mentioning
confidence: 99%
“…Test-retest reliabilities 114 for average percept duration are moderate to high, with past stud-115 ies reporting r s = 0.69 (Whittle, 1963), r p = 0.7 (Miller et al, 2010) 116 and r p = 0.8 (Pettigrew & Miller, 1998, in bipolar patients and 117 controls). 118 Variability in rate of rivalry has been found to correlate with 119 patterns of saccadic eye movements (Hancock et al, 2012), with 120 level of dichoptic masking (Baker & Graf, 2009), with retinotopic 121 activity in extrastriate visual cortex triggered by the suppressed 122 image (Yamashiro et al, 2014), and with variability in the structure 123 of parietal cortex (Kanai, Bahrami, & Rees, 2010). Rate of rivalry is 124 faster in children than adults (Hudak et al, 2011;Kovacs & 125 Eisenberg, 2004) and declines with increasing age in adulthood 126 (Jalavisto, 1964;Ukai, Ando, & Kuze, 2003).…”
Section: Stereopsis 23mentioning
confidence: 99%
“…Past work has identified neural factors unrelated to oscillatory activity that predicts percept duration. These include the strength of response to the suppressed stimulus (Yamashiro et al, 2014), cortical thickness of the superior parietal lobule (Kanai et al, 2010), and the number of energy minima in visual cortex (Watanabe et al, 2014). Transcranial magnetic stimulation disruption of parietal cortex has also been shown to alter of percept durations, though past studies have found both increased and decreased durations (Carmel, Walsh, Lavie, & Rees, 2010;Zaretskaya, Thielscher, Logothetis, & Bartels, 2010).…”
Section: Other Factors Predicting Perceptual Stabilitymentioning
confidence: 99%
“…Relatively little is known about the neural bases for these individual differences (Kleinschmidt, Sterzer, & Rees, 2012). A few studies using structural and functional magnetic resonance imaging have examined brain regions underlying individual differences in perceptual stability (Kanai, Bahrami, & Rees, 2010;Watanabe, Masuda, Megumi, Kanai, & Rees, 2014;Yamashiro et al, 2014). However, despite perceptual durations being a time-domain measure, little is known about how they relate to dynamic neural processes.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have explored individual differences in the dynamics of binocular rivalry identify a number of interesting associated factors (for a review see Kleinschmidt et al, 2012). For example, differences in rivalry rate have been linked to variations in density and thickness of the parietal cortex (Kanai et al, 2010), activity in early visual area (Yamashiro et al, 2014), gaze movements using static binocular rivalry gratings (Hancock et al, 2012; however, when using drifting binocular gratings the results was not replicated by Law et al (2015) and GABA concentration in visual cortex (van Loon et al, 2013). Studies have also suggested a genetic basis for this variability, supported by identical twins showing greater similarity in rivalry dynamics than non-identical twins (Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%